Implementasi Nilai Akhlak Di Sekolah Islam Terpadu (Penelitian Di SDIT Permata Bunda 2 Bandar Lampung) - yamin, sabanul (Sekolah Tinggi Ilmu Tarbiyah Darul Fattah, 2023)
To answer the current challenge of moral degradation, implementing (Hardiansyah & Mas’odi, 2020; Syafiqurrohman, 2020) moral values ​​at Integrated Islamic School (Research at SDIT Permata Bunda II Bandar Lampung) is something that is very important in the lives of students, especially at school. The purpose of this research is to identify and explore the transformation process of moral values ​​at SDIT Permata Bunda II Bandar Lampung. This research method is a qualitative descriptive method with data collection tools, namely observation and interviews, to one school principal and one PAI subject teacher. The findings of this study are that there has been an implementation of moral values ​​through school programs including; Congregational prayers, memorization of 2 chapters of the Qur'an, alms, Islamic Boarding School Ramadhan, MPLS (Introduction to School Environment, social service and nature tadabbur). The implementation of the program produces two main moral values, namely: divine values ​​(faith and piety), humanity ( discipline, responsibility, care for others, optimism and self-confidence).The process of implementing moral values ​​uses three stages, namely: value transformation (understanding), value transaction (understanding), value trans internalization (practice). Keywords: Implement, Moral Values, Integrated Islamic School